"PAUSE": a method for communicating radiological extent of peritoneal malignancy. Issue 11 (November 2017) - Chandramohan, A.; Thrower, A.; Smith, S.A.; Shah, N.; Moran, B.
Abstract : Radiology reports of diffuse peritoneal disease should address key findings pertinent to the management of these patients. The reporting of radiology findings in patients with peritoneal malignancy is currently variable and poorly standardised. Using the acronym "PAUSE" we emphasise the key imaging features that a radiology report should include in a patient with peritoneal malignancy, focussing on the key elements determining feasibility and likely prognosis of surgery and potential benefits from cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). The term "PAUSE" incorporates the following: P, primary tumour and peritoneal carcinomatosis index (PCI) as estimated by imaging; A, ascites and abdominal wall involvement; U, unfavourable sites of involvement; S, small bowel and mesenteric disease; E, extra peritoneal metastases. Thus, "PAUSE" has the potential to standardise radiology reporting in this field.